A fluorescence "off–on–off" sensing platform based on bimetallic gold/silver nanoclusters for ascorbate oxidase activity monitoring. Issue 3 (12th December 2019) - Wang, Mengjun; Wang, Mengke; Wang, Guannan; Su, Xingguang
Abstract : A novel papain-capped Au/Ag NCs was successfully synthesized and applied for AAO activity detection. Abstract : Herein, papain-protected bimetallic gold/silver nanoclusters (Au/Ag NCs) were successfully synthesized and applied for the detection of ascorbate oxidase (AAO). The doping of papain-protected Au nanoclusters with Ag enhanced the fluorescence intensity with an intense red fluorescence peak at 617 nm, and the red-emitting Au/Ag nanoclusters were further used to monitor the AAO activity. The fluorescence of Au/Ag NCs could be quenched by hydrogen peroxide (H2 O2 ) due to the generation of hydroxyl radicals (˙OH) from the reaction of Ag/Au nanoclusters and H2 O2 . However, the addition of ascorbic acid (AA) effectively reacted with the free radicals and caused the fluorescence recovery of the Au/Ag NCs. Furthermore, AAO could catalyze the oxidation of AA to form dehydro-ascorbate (DHA). As a result, there was not enough AA to consume the hydroxyl radicals, which resulted in a decrease in the fluorescence of the papain-capped Au/Ag NCs. Therefore, the AAO activity can be monitored by measuring the fluorescence intensity of the red-emitting Au/Ag NCs. Moreover, the developed method for AAO detection displayed a good linear relationship from 5 to 80 mU mL −1 and the detection limit was 1.72 mU mL −1 . Thus, a simple and selective method for the determination of the AAO activity was constructed and satisfactory results were obtained in real sample detection.